Asymmetric cobalt catalysts for hydroboration of 1, 1-disubstituted alkenes. Issue 11 (2nd December 2014) - Chen, Jianhui; Xi, Tuo; Ren, Xiang; Cheng, Biao; Guo, Jun; Lu, Zhan
Abstract : Chiral iminopyridine oxazoline (IPO) ligands were designed, synthesized and utilized for the first cobalt-catalyzed highly regio- and enantioselective anti-Markovnikov hydroboration of 1, 1-disubstituted aryl alkenes. These novel IPO ligands will likely be of high value for asymmetric transformations with first-row transition metals. Abstract : Chiral iminopyridine oxazoline (IPO) ligands were designed, synthesized and utilized for the first cobalt-catalyzed highly regio- and enantioselective anti-Markovnikov hydroboration of 1, 1-disubstituted aryl alkenes. These novel IPO ligands will likely be of high value for asymmetric transformations with first-row transition metals.